Geomechanics Numerical Simulation of Stress Changes for Permanent Plug and Abandonment in Montney Shale Formation, British Columbia - Low, H.L. (American Rock Mechanics Association (ARMA), 2021)
Over 48 of the 300 operating platforms in Malaysia had been highlighted to be exceeding the initial design life of 25 years and entering the decommissioning phase in the next ten years. As part of the decommissioning activities, the well plugging and abandonment (P&A) is a vital phase in establishing long-term isolation of the downhole fluid that may contribute to 45 of the total decommissioning cost. Despite the expensive expenditure, cases of leakage due to cement plug failure have been reported which caused great impacts towards the remedial cost and Health, Safety and Environment (HSE) issues. From the investigation, the possible major cause of failures which are caused by the effects of rock mechanics and in-situ stress changes. Therefore, the study is aimed to perform a field-scale geomechanics analysis for well plugging and abandonment activity. A parametric study on the rock properties and reservoir condition are conducted to investigate the risks of plug failure, which included the rocksâ Youngâs Modulus, Poisson Ratio, porosity, permeability and reservoir abandonment pressure A Finite Element Model (FEM) simulation is established based on an actual horizontal well in the Lower Montney Formation in British Columbia, Canada. The model is validated by conducting the mesh dependency study, comparison of the simulated bottom-hole pressure (BHP) with field BHP during hydraulic fracturing propagation and the well BHP during the cementing process of the well plug and abandonment activities. Mohr-Coulomb Failure Criterion is adopted in studying the risks of plug failure by establishing the circle of stresses exerted on the rock and cement annulus bodies. The result depicts that significant stress and strain changes occur during the well P&A operation that greatly reduces the effective stress in the rock and cement annulus. The well P&A cementing operation had imposed great effective stress changes (3.7 MPa) in both the cement annulus and near-wellbore formations. For strike-slip fault regime, most effective stresses changes were observed in the direction of the minimum horizontal stress which aligned with the direction of the hydraulic fracture. The risks of cement annulus failure increased exponentially in a tight stimulated reservoir section (extremely low-permeability) and high abandonment pressure. Â© 2021 ARMA, American Rock Mechanics Association.